Prevalence of anti–platelet factor 4/polyanionic antibodies after COVID‐19 vaccination with ChAdOx1 nCoV‐19 and CoronaVac in Thais. Issue 7 (11th October 2021) - Noikongdee, Phichchapha; Police, Pornnapa; Phojanasenee, Tichayapa; Chantrathammachart, Pichika; Niparuck, Pimjai; Puavilai, Teeraya; Phuphuakrat, Angsana; Angchaisuksiri, Pantep; Boonyawat, Kochawan
Abstract: Introduction: Vaccine‐induced thrombotic thrombocytopenia (VITT) has been reported after vaccination with the adenoviral vector coronavirus disease 2019 (COVID‐19) vaccine ChAdOx1 nCoV‐19 in European countries. To date, two cases of VITT have been reported in Thais after COVID‐19 vaccination. We determined the frequency of anti–platelet factor 4 (PF4)/polyanionic antibodies in the Thai population receiving the COVID‐19 vaccines. Methods: We conducted a cross‐sectional study to evaluate the prevalence of anti‐PF4/polyanionic antibodies in health care workers who received COVID‐19 vaccination with ChAdOx1 nCoV‐19 or CoronaVac within 7 to 35 days. A control population who had not been vaccinated was also included. Anti‐PF4/polyanionic antibodies were detected using ELISA. Functional assay with platelet aggregation was performed for all positive anti‐PF4/polyanionic antibody ELISA tests. Results: A total of 646 participants were included in the study; 221 received ChAdOx1 nCoV‐19, 232 received CoronaVac, and 193 participants were in the control group. The prevalence of anti‐PF4 antibodies was 2.3% (95% confidence interval [CI], 0.7‐5.2), 1.7% (95% CI, 0.5‐4.4) in the ChAdOx1 nCoV‐19 and CoronaVac groups, respectively. There was no positive test in the control group. None of the PF4/polyanionic positive sera induced platelet aggregation. Conclusion: We found a low prevalence of anti‐PF4 antibodies in Thais after vaccination with ChAdOx1 nCoV‐19 and CoronaVac. None of the antibodies were functional and lacked an association with VITT.